The formation of adjacent triplex-duplex domainsin DNA. - Nam, K H (1999)
The ability of single-stranded DNA oligomers to form adjacent triplex and duplex domains with two DNA structural motifs was examined. Helix-coil transition curves and a gel mobility shift assay were used to characterize the interaction of single-stranded oligomers 12-20 nt in length with a DNA hairpin and with a DNA duplex that has a dangling end. The 12 nt on the 5'-ends of the oligomers could form a triplex structure with the 12 bp stem of the hairpin or the duplex portion of the DNA with a dangling end. The 3'-ends of the 17-20 nt strands could form Watson-Crick pairs to the five base loop of the hairpin or the dangling end of the duplex. Complexes of the hairpin DNA with the single-stranded oligomers showed two step transitions consistent with unwinding of the triplex strand followed by hairpin denaturation. Melting curve and gel competition results indicated that the complex of the hairpin and the 12 nt oligomer was more stable than the complexes involving the extended single strands. In contrast, results indicated that the extended single-stranded oligomers formed Watson-Crick base pairs with the dangling end of the duplex DNA and enhanced the stability of the adjacent triplex region.